E–writing activity using Instant Messaging to ignite EFL students’ critical thinking in writing English argumentation on a conservation issue - Rohayati, Dedeh; Kosasih, Fauzy Rachman (Interdisciplinary International Journal of Conservation and Culture, 2023)
The 21st-century skill has intrigued all stakeholders in the education context and educational practitioners have a great decision to ignite the implementation of critical thinking in the classroom. This brings the present study to be carried out with the aim of exploring 1) the argument analysis of critical thinking demonstrated by the EFL students in writing argumentative text using Instant Messaging; and 2) students’ awareness of the relationship among argumentative text, critical thinking, conservation issue and some challenges in experiencing the activity Instant Messaging. The present study involved five EFL students enrolling in Academic writing in the fifth semester. The qualitative case study theory was utilized so that the primary data was obtained by employing screenshots of students’ written argumentation and interview (Instants Messaging Interview). The present study came up with evidence that the quality of students’ arguments was not contented. The obvious premises and conclusion are not offered to build a good argument. It is to say that a student’s ability to write argumentative text as a tool facilitates students’ critical thinking and needs more ignition. Consequently, students’ ability in thinking critically also needs improvement. Another result reveals that the inclusion of technical support such as internet access and an E-writing device, namely, instant messaging, helped them a lot in making judgments fast. Searching from Google search in one click made them more aware of several issues in a concise time such as the term critical thinking, strategy in writing a good argumentative text, effects caused by plastic and its recommendation, and offering some alternatives for some challenges. Thus, students experienced technical support as a great assistance to attach accurate data for their writing of Argumentative text effectively and efficiently.